2011
DOI: 10.1016/j.jalz.2011.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Direct comparison of fluorodeoxyglucose positron emission tomography and arterial spin labeling magnetic resonance imaging in Alzheimer's disease

Abstract: BACKGROUND The utility flourodeoxyglucose PET (FDG-PET) imaging in Alzheimer’s Disease (AD) diagnosis is well established. Recently, measurement of cerebral blood flow using arterial spin labeling MRI (ASL-MRI) has shown diagnostic potential in AD, though it has never been directly compared to FDG-PET. METHODS We employed a novel imaging protocol to obtain FDG-PET and ASL-MRI images concurrently in 17 AD patients and 19 age-matched controls. Paired FDG-PET and ASL-MRI images from 19 controls and 15 AD patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
129
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 156 publications
(140 citation statements)
references
References 26 publications
(27 reference statements)
8
129
0
3
Order By: Relevance
“…Despite these limitations, the practical clinical implications of this report add to other reports25, 26, 27 suggesting that ALS‐MRI has a similar sensitivity and specificity to FDG‐PET for detecting brain changes due to AD and bvFTD. MRI examinations are noninvasive without ionizing radiation.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Despite these limitations, the practical clinical implications of this report add to other reports25, 26, 27 suggesting that ALS‐MRI has a similar sensitivity and specificity to FDG‐PET for detecting brain changes due to AD and bvFTD. MRI examinations are noninvasive without ionizing radiation.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, prior studies have indicated that the diagnostic value of ASL‐MRI is similar to that of FDG‐PET in AD 25, 26. Several prior studies have shown that patterns of perfusion are different in AD and bvFTD,18, 19, 20 and one prior study from Europe has supported the idea that diagnostic value of ASL‐MRI is similar to the diagnostic value of FDG‐PET 19.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…These co-registered images were spatially normalized to a MNI atlas space. The partial volume correction was performed using results with more than 25% of the maximal regional intensity [17]. The mean standard uptake value ratio (SUVr) in the cerebellum GM was used as a reference.…”
Section: Pet Analysesmentioning
confidence: 99%